Conflicts and tensions - Anheier, Helmut K., 1954-; Isar, Yudhishthir Raj.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2007)
Analyzing the relationship between globalization and cultures this title tracks cultural trends in all regions of the world covering issues ranging from the role of cultural difference in politics and governance to heritage conservation, artistic expression and the cultural industries.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Culture conflict; Culture and globalization; Electronic books